Aragonite fiber and preparation method thereof, cement-based material and cement product

A controlled precipitation method using calcium ions, urea, and catalysts with additives induces aragonite fibers in cement-based materials, improving mechanical strength and crack resistance by ensuring high yield and uniform distribution.

CN119240771AActive Publication Date: 2025-01-03SHENZHEN UNIV

Patent Information

Application Number
CN202411394009.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing methods for preparing aragonite fibers in cement-based materials face challenges in controlling crystal morphology and yield, leading to poor durability and crack resistance due to the instability of vaterite and calcite, and the uneven distribution and bonding of microfibers.

Method used

A controlled precipitation method using calcium ions, urea, and a catalyst, with optional additives like amylose, magnesium ions, and sulfate ions, to induce aragonite crystal formation as microfibers, inhibiting other crystal variants and maintaining stability at controlled temperatures.

Benefits of technology

The method produces aragonite fibers with a high yield and good dispersion, enhancing the mechanical strength, toughness, and crack resistance of cement-based materials by forming a three-dimensional mesh that prevents crack propagation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240771A_ABST
    Figure CN119240771A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic non-metallic materials, in particular to aragonite fibers, a preparation method of the aragonite fibers, a cement-based material and a cement workpiece. The preparation method comprises the following steps: preparing raw materials including calcium ions, urease and urea into a mixed solution, and carrying out precipitation reaction to obtain aragonite fibers; wherein the mixed solution further comprises at least one of amylose, magnesium ions and sulfate ions, and the temperature of the mixed solution is lower than or equal to 50 DEG C. The catalyst promotes urea hydrolysis to generate carbonate ions, and then the carbonate ions and calcium ions generate calcium carbonate precipitates. On one hand, amylose, magnesium ions and sulfate ions can induce calcium ions and carbonate ions to generate aragonite crystals and inhibit generation of other allotropic variants; on the other hand, aragonite crystals can be induced to precipitate in a microfiber form, generation of rodlike fibers is promoted, and generation of particles in other micromorphologies is inhibited. The prepared aragonite fiber has a good microfiber form, is not easy to agglomerate, and can be used for reinforcing a cement-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic non-metallic materials, and in particular to aragonite fibers and preparation methods thereof, cement-based materials, and cement parts. Background Art

[0002] Traditional cement-based materials often face problems such as insufficient durability and poor crack resistance during use, which limits their service life and scope of application. Existing studies have found that the addition of microfibers can reinforce cement-based materials, with good reinforcement effects and low costs. For example, the physical doping method physically mixes microfibers such as polypropylene fibers, steel fibers and glass fibers with cement-based materials, but there are problems such as uneven fiber distribution and insufficient fiber-matrix bonding. For example, the chemical synthesis method introduces polymer monomers into cement-based materials for in-situ polymerization to form a reinforcing phase, but the reaction conditions are harsh, the process is complex, and the cost is high. For example, microbial mineralization technology can improve the performance of cement-based materials by inducing the crystallization of calcium carbonate minerals through microorganisms such as urease-positive bacteria.

[0003] During the microbial mineralization process, the morphology and size of mineral crystals are difficult to control precisely, which will affect the mechanical properties and durability of cement-based materials. Since calcium carbonate crystals have a variety of isomorphic variants, such as vaterite, aragonite, and calcite, vaterite is very unstable and easily converted into calcite when heated. Calcite has the most stable properties, but its common microscopic morphology is mainly flaky and blocky aggregates. The common microscopic morphology of vaterite is mainly spherical aggregates, neither of which can be used as microfibers in cement-based materials.

[0004] Although aragonite has the best compatibility with cement-based materials and is slightly more stable than vaterite, it is also in a metastable state and is easily converted into stable calcite. Therefore, the existing preparation methods are prone to generate a large amount of calcite when preparing aragonite, reducing the yield of aragonite; and aragonite also has a variety of microscopic forms, such as rod-shaped (needle-shaped, fibrous), radial, stalactite-shaped, bean-shaped, etc. The existing preparation methods are difficult to control the microfiber morphology generated by aragonite, reducing the yield of aragonite fibers. Summary of the invention

[0005] The purpose of the present application is to provide aragonite fiber and a preparation method thereof, aiming to solve the technical problem that it is difficult to prepare aragonite fiber by the existing preparation method.

[0006] Another object of the present application is to provide cement-based materials and cement products, aiming to solve the technical problem that the prior art microfibers are not ideal for improving the performance of cement-based materials.

[0007] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0008] In a first aspect, the present application provides a method for preparing aragonite fiber, comprising the following steps:

[0009] The raw materials including calcium ions, urease and urea are prepared into a mixed solution for precipitation reaction to obtain aragonite fibers;

[0010] The mixed solution also includes at least one of amylose, magnesium ions and sulfate ions.

[0011] The preparation method of the present application promotes the hydrolysis of urea to generate carbonate ions through the catalyst in the mixed solution, and then generates calcium carbonate precipitation with calcium ions. In addition, at least one of the amylose, magnesium ions, and sulfate ions included in the mixed solution can induce calcium ions and carbonate ions to generate aragonite crystals on the one hand, and inhibit the generation of other isomorphous variants such as vaterite and calcite crystals; on the other hand, aragonite crystals can be induced to precipitate in the form of microfibers, promote the generation of rod-shaped fibers, and inhibit the generation of radial, bean-shaped and other microscopic morphological particles, thereby increasing the yield of aragonite fibers. At the same time, the temperature of the mixed solution is also controlled to reduce the conversion of aragonite crystals to calcite crystals and increase the yield of aragonite fibers. Therefore, the preparation method of the present application is process-controllable, the yield of aragonite fibers is high, has a good microfiber morphology, has a large aspect ratio, a small specific surface area and internal stress, and therefore, the aragonite fibers obtained are not easy to agglomerate and can be used to strengthen cement-based materials.

[0012] In a second aspect, the present application provides an aragonite fiber, wherein the aragonite fiber is prepared by the preparation method of the above-mentioned application.

[0013] The aragonite fiber of the present application is aragonite crystal, has good compatibility with cement-based materials, and is in the form of microfibers, has a high aspect ratio and a small specific surface area in size, so the cohesion is small, the dispersion is good, and it is not easy to agglomerate into large particles. It can be used in cement-based materials to significantly play the modification effect of microfibers and improve crack resistance. At the same time, the chemical composition of aragonite fiber is mainly calcium carbonate, which can improve working performance and strength as an admixture. In summary, the aragonite fiber of the present application embodiment can improve the mechanical strength, toughness and durability of cement-based materials.

[0014] In a third aspect, the present application provides a cement-based material, including a cement material, and also including aragonite fibers prepared by the preparation method described in the above text application or aragonite fibers described in the above text application.

[0015] The aragonite fiber in the cement base of the present application has good compatibility with cement materials, and the rod-shaped aragonite fiber is not easy to adsorb and agglomerate into large particles, has good dispersibility, and can be evenly distributed in the cement material. Therefore, the cement-based material can give full play to the modification effect of the fiber on the cement material and improve the crack resistance. At the same time, the chemical composition of aragonite fiber is mainly calcium carbonate, which can improve the working performance and increase the strength as an admixture. In summary, the cement-based material of the embodiment of the present application has high mechanical strength, crack resistance, and durability.

[0016] In a fourth aspect, the present application provides a cement component, which is obtained by hydrating the cement-based material of the above-mentioned application.

[0017] The present application cement parts are prepared by hydration treatment of the above cement-based materials, and aragonite fibers, as nucleation sites of cement hydration products, can accelerate cement hydration, promote the formation of cement hydration products, and thus improve its mechanical properties. After the cement material hardens, the aragonite fibers are uniformly filled and combined in the cement parts. When the cement parts are subjected to external tension, pressure, and bending force, these aragonite fibers can coordinate the solidified cement to absorb and migrate stress, further improve the mechanical strength of the cement parts, especially improve tensile, compressive, and bending resistance. In addition, these aragonite fibers form a three-dimensional mesh distribution in the cement parts, which can effectively reduce the generation of microcracks inside the cement parts. When the cement parts are subjected to large stresses to produce fine cracks, the aragonite fibers are connected across the cracks to prevent the cracks from further growing and propagating, further improving the toughness and crack resistance of the cement parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 This is a 2000-fold magnified SEM image of the aragonite fiber in Example A1 of the present application;

[0020] Figure 2 This is a 10,000-fold magnified SEM image of the aragonite fiber in Example A1 of the present application;

[0021] Figure 3 This is a 2000-fold magnified SEM image of the calcite in comparative example A1 of the present application;

[0022] Figure 4 This is a 10,000-fold magnified SEM image of the calcite in comparative example A1 of the present application;

[0023] Figure 5This is a 2000-fold magnified SEM image of vaterite in Comparative Example A1 of the present application;

[0024] Figure 6 This is a 10,000-fold magnified SEM image of vaterite in comparative example A1 of the present application. DETAILED DESCRIPTION

[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0026] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0027] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.

[0028] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0029] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.

[0030] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0031] The concentration in this application refers to mass concentration. For example, a calcium ion concentration of 3% means that the mass of calcium ions in the entire solution accounts for 3%.

[0032] A first aspect of an embodiment of the present application provides a method for preparing aragonite fiber, comprising the following step S10:

[0033] S10. The raw materials including calcium ions, urea and a catalyst are prepared into a mixed solution for precipitation reaction to obtain aragonite fibers;

[0034] The mixed solution further includes at least one of amylose, magnesium ions and sulfate ions, and the temperature of the mixed solution is ≤50°C.

[0035] The preparation method of the embodiment of the present application promotes the hydrolysis of urea to generate carbonate ions through the catalyst in the mixed solution, and then generates calcium carbonate precipitation with calcium ions. At least one of the amylose, magnesium ions, and sulfate ions included in the mixed solution can induce calcium ions and carbonate ions to generate aragonite crystals on the one hand, and inhibit the generation of other isomorphous variants such as vaterite and calcite crystals; on the other hand, aragonite crystals can be induced to precipitate in the form of microfibers, promote the generation of rod-shaped fibers, and inhibit the generation of radial, bean-shaped and other microscopic morphological particles, thereby increasing the yield of aragonite fibers. At the same time, the temperature of the mixed solution is also controlled to reduce the conversion of aragonite crystals to calcite crystals and increase the yield of aragonite fibers. Therefore, the preparation method of the embodiment of the present application is process-controllable, and the yield of aragonite fibers is high, with good microfiber morphology, with a large aspect ratio, a small specific surface area and internal stress, and therefore, the aragonite fibers obtained are not easy to agglomerate, and can be used to strengthen cement-based materials.

[0036] About calcium ions:

[0037] The concentration of calcium ions in the mixed solution will directly affect the nucleation and growth rate of calcium carbonate aragonite crystals. In some embodiments, in the mixed solution, the concentration of calcium ions is 0.5mol / L to 2.0mol / L, which may include but is not limited to any value of 0.5mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L or the range between any two values. The above concentration of calcium ions is conducive to inducing the formation of microfibers and improving the yield of aragonite fibers. If the concentration of calcium ions is too low, it may promote the formation of tiny nanoscale calcium carbonate particles and reduce the yield of aragonite fibers. If the concentration is too high, it may lead to the formation of larger crystal particles, reducing the yield of microfiber morphology aragonite fibers.

[0038] The source of calcium ions can be common soluble calcium salts, such as calcium chloride, dissolved in a mixed solution, or extracted from common industrial solid wastes, such as extracted from waste concrete with hydrochloric acid, or obtained by a second extraction treatment with water, hydrochloric acid, sodium hydroxide solution, ammonium chloride solution or other solvents or extraction solutions from industrial solid wastes such as phosphogypsum, steel slag, and recycled micropowder. During extraction, the industrial solid waste and the extraction solution can be mixed in a solid-liquid mass ratio of 1: (1 to 10). The extraction can be carried out at room temperature. During extraction, the solid and liquid are mixed and stirred for 6 to 12 hours, and then the supernatant is filtered and retained to obtain a solution containing calcium ions.

[0039] About urea:

[0040] Urea can react with water under the action of a catalyst to generate ammonia and carbon dioxide, obtain carbonate ions in the solution, and then react with calcium ions to promote the nucleation and growth of calcium carbonate crystals to generate precipitation. In some embodiments, in the mixed solution, the concentration of urea is 0.5mol / L to 2.0mol / L, which may include but is not limited to any value of 0.5mol / L, 1.0mol / L, 1.5mol / L, and 2.0mol / L or the range between any two values. Urea at the above concentration is conducive to inducing the formation of microfibers and improving the yield of aragonite fibers. If the urea concentration is too low, too little precipitation is generated. If the concentration is too high, amorphous calcium carbonate may be generated, which is unstable in nature and reduces the yield of aragonite crystals.

[0041] About Catalyst:

[0042] The catalyst can cause urea to undergo a hydrolysis reaction in the solution to obtain carbonate ions, thereby generating calcium carbonate precipitation. The catalyst may include urease, which has a high degree of specificity and can catalyze the hydrolysis of urea into ammonia and carbonate ions. The urease may be a microbial urease provided by a microorganism, such as Bacillus pasteurianus, Bacillus subtilis, etc. Urease can also be extracted from animals and plants, and the first extraction treatment can be optionally performed from plants such as sword beans and soybeans. The first extraction treatment method can be extracted by centrifugation with water. Specifically, soybeans can be weighed and dried at room temperature, and the soybeans can be crushed using a crushing device. After crushing, the soybean powder is sieved; the sieved soybean powder is weighed and mixed with deionized water, and fully stirred to obtain a soybean powder solution, which is centrifuged using a centrifuge. The temperature of the centrifuge can be 20°C, and the speed can be 4000r / min. The bottom sediment after centrifugation is discarded, and the supernatant is retained and filtered to obtain a solution containing soybean urease.

[0043] In some embodiments, in the mixed solution, the concentration of the catalyst is 20 g / L to 50 g / L. It may include but is not limited to any value of 20 g / L, 30 g / L, 40 g / L, 50 g / L or a range between any two values. The catalyst of the above concentration is beneficial to catalyze urea to generate carbonate ions of appropriate concentration, increase the nucleation rate and growth rate of calcium carbonate crystals, induce the formation of microfibers, and increase the yield of aragonite fibers. If the catalyst concentration is too low, too little precipitation is generated. If the concentration is too high, amorphous calcium carbonate may be generated, which is unstable in nature and reduces the yield of aragonite crystals.

[0044] Compared with the uncontrollability of direct precipitation with calcium ions and carbonate ions, the preparation method of the present application uses calcium ions, urea, and catalysts for precipitation reaction, which belongs to the mineralization reaction to induce the formation of calcium carbonate crystals, and can better control the reaction conditions to regulate the formation of aragonite fibers. Since the concentrations of the above-mentioned calcium ions, urea, and catalysts will affect the nucleation rate and growth rate of calcium carbonate crystals and the formation of aragonite fibers, the effect of the reaction can be improved by controlling the ratio of the three. In some embodiments, in the mixed solution, the mass ratio of calcium ions, urea, and catalysts is 1: (0.5-2): (1-5), and in the exemplary examples, it can include but is not limited to 1: (0.5 or 1 or 2): (1 or 2 or 3 or 5) any ratio or the range between any two ratios. The raw materials of these ratios are conducive to improving the yield of aragonite fibers.

[0045] In some embodiments, in order to evenly mix the solutes in the mixed solution for precipitation reaction, it is optional to prepare each solute into a solution and then mix it into a mixed solution. Among them, the concentration of the calcium ion solution can be 0.5mol / L~2.0mol / L, the concentration of the catalyst solution can be 20~50g / L, and the concentration of the urea solution can be 0.5~2.0mol / L, and then the calcium ion solution, the catalyst solution, and the urea solution are mixed in a volume ratio of 1: (0.5~2): (1~5) to perform precipitation reaction.

[0046] About amylose, magnesium ions, and sulfate ions:

[0047] At least one of the three components can act as a crystal stabilizer in the precipitation reaction, which is conducive to inducing the formation of aragonite crystals from calcium ions and carbonate ions during the precipitation reaction, and inhibiting the formation of other isomorphous variants such as vaterite and calcite crystals; it is also conducive to inducing the precipitation of aragonite crystals in the form of microfibers, promoting the formation of rod-shaped fibers, and increasing the yield of aragonite fibers. If the above-mentioned crystal stabilizer is lacking, a large amount of vaterite and calcite crystals may be generated, and the generated aragonite crystals are also prone to generate various shapes such as radial, stalactite, bean-shaped, etc., which reduces the yield of microfiber-shaped aragonite.

[0048] These components can be added to the mixed solution together with raw materials such as calcium ions during the mixing process. One of amylose, magnesium ions, and sulfate ions, or any two or all three can be added.

[0049] In some embodiments, when the mixed solution contains amylose, the concentration of amylose is 2% to 5%, where % is the mass ratio concentration. Amylose can be obtained by extraction from plants such as corn and beans. The extraction method can refer to the above-mentioned method of extracting urease from soybeans through the first extraction treatment. This extraction method can not only extract urease from soybeans, but also extract amylose, promote the formation of aragonite fiber in the precipitation reaction, and improve the yield.

[0050] In some embodiments, when the mixed solution contains magnesium ions, the concentration of magnesium ions is 0.01 mol / L to 0.1 mol / L, and magnesium ions can be provided by adding soluble magnesium salts to the mixed solution, such as magnesium chloride, magnesium sulfate, etc. In some embodiments, when the mixed solution contains sulfate ions, the concentration of sulfate ions is 0.01 mol / L to 0.1 mol / L, and sulfate ions can be provided by adding soluble sulfates to the mixed solution. In addition, reference can be made to the above-mentioned method of preparing phosphogypsum through the second extraction treatment, and calcium ions and sulfate ions can be obtained from phosphogypsum.

[0051] In some embodiments, the temperature of the mixed solution is ≤50°C to prevent the temperature from being too high, which may cause the aragonite crystals to transform into stable calcite crystals. Furthermore, the temperature of the mixed solution is 20-50°C, and may be any value of 20°C, 30°C, 40°C, or 50°C, or a range between any two values. Limiting the mixed solution to the above temperature can promote the activity of the catalyst, increase the nucleation rate and growth rate of calcium carbonate crystals, and improve the stability of aragonite fibers generated by precipitation reactions. If the temperature is too high, it may promote the transformation of aragonite crystals into stable calcite, reducing the yield of aragonite fibers.

[0052] In some embodiments, the precipitation reaction time is 1 to 3 hours, which can be any value of 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or a range between any two values. The above reaction time is conducive to inducing the nucleation and growth process of calcium carbonate and improving the yield of aragonite fiber. If the reaction time is too long, it may promote the formation of a larger particle calcium carbonate crystal structure, and it may also promote the transformation of aragonite crystals to stable calcite crystals.

[0053] After the above precipitation reaction is completed, aragonite fiber can be obtained through solid-liquid separation treatment. The aragonite fiber prepared by the above method has a needle-rod-shaped microfiber structure, a high aspect ratio and a small specific surface area, good dispersion and is not easy to agglomerate. It can be used in cement-based materials to significantly improve the mechanical properties of cement-based materials.

[0054] A second aspect of the embodiments of the present application provides an aragonite fiber, and the aragonite fiber is prepared by the preparation method of the embodiments of the present application as described above.

[0055] The aragonite fiber of the embodiment of the present application is aragonite crystal, has good compatibility with cement-based materials, and is in the form of microfibers, has a high aspect ratio and a small specific surface area in size, so the cohesion is small, the dispersion is good, and it is not easy to agglomerate into large particles. It can be used in cement-based materials to significantly play the modification effect of microfibers and improve crack resistance. At the same time, the chemical composition of aragonite fiber is mainly calcium carbonate, which can improve working performance and strength as an admixture. In summary, the aragonite fiber of the embodiment of the present application can improve the mechanical strength, toughness and durability of cement-based materials.

[0056] As an example of the present application, a SEM image of aragonite fiber magnified 2000 times is shown in FIG. Figure 1 As shown, the SEM image magnified 10000 times is as follows Figure 2 As shown, from Figure 1 , Figure 2 It can be seen that the aragonite fibers are in the form of rod-shaped microfibers with clear shapes and almost no agglomeration or entanglement.

[0057] After testing, in some embodiments, the aspect ratio of the aragonite fiber is (3-6):1, which may include but is not limited to any ratio of 3:1, 4:1, 5:1, 6:1 or any range between two ratios, forming a rod-shaped microfiber shape, which is easier to agglomerate into secondary particles than a shape with a smaller aspect ratio. These rod-shaped microfibers with aspect ratios are easier to disperse evenly and are not prone to agglomeration, which is conducive to uniform dispersion in the cement matrix. Among them, the length of the aragonite fiber can be 7-15μm; it can include but is not limited to any value of 7μm, 8μm, 10μm, 15μm or any range between two values.

[0058] In some embodiments, the specific surface area of ​​the aragonite fiber is 0.3 to 0.5 m 2 / g, including but not limited to 0.3m 2 / g, 0.4m 2 / g, 0.45m 2 / g, 0.5m 2 / g any value or the range between any two values. Compared with the microscopic shapes with high specific surface area such as spheres and flakes, the surface adsorption of rod-shaped aragonite with relatively small specific surface area is weaker and it is not easy to adsorb and agglomerate together. Therefore, it is easier to disperse when used in cement-based materials.

[0059] A third aspect of the embodiments of the present application provides a cement-based material, including cement material, and also including aragonite fiber prepared by the preparation method of the embodiments of the present application or aragonite fiber of the embodiments of the present application.

[0060] The aragonite fiber in the cement-based embodiment of the present application has good compatibility with the cement material, and the rod-shaped aragonite fiber is not easy to adsorb and agglomerate into large particles, has good dispersibility, and can be evenly distributed in the cement material. Therefore, the cement-based material can give full play to the modification effect of the fiber on the cement material and improve the crack resistance. At the same time, the chemical composition of aragonite fiber is mainly calcium carbonate, which can improve the working performance and increase the strength as an admixture. In summary, the cement-based material of the embodiment of the present application has high mechanical strength, crack resistance, and durability.

[0061] In some embodiments, the mass ratio of cement material to aragonite fiber is (2-4):1, which may include but is not limited to any ratio of 2:1, 2.5:1, 3:1, 4:1 or a range between any two ratios. In addition, the cement-based material may also include ingredients such as aggregate, auxiliary cementitious materials, and water reducers, which are mixed in a reasonable ratio. These raw materials may also contain magnesium ions and sulfate ions to further inhibit the conversion of aragonite fiber to calcite. When the cement-based material and water are prepared into a slurry, the water-cement ratio can be (2-4):1, and because the aragonite fiber has a rod-like structure, it has better fluidity in the cement slurry, which is further conducive to the uniform dispersion of the aragonite fiber in the cement slurry.

[0062] A fourth aspect of the embodiments of the present application provides a cement component, which is obtained by hydrating the cement-based material of the embodiments of the present application.

[0063] The cement parts of the present application embodiment are prepared by hydration treatment of the above cement-based materials, and aragonite fibers, as nucleation sites of cement hydration products, can accelerate cement hydration, promote the formation of cement hydration products, and then improve its mechanical properties. After the cement material hardens, the aragonite fibers are uniformly filled and combined in the cement parts. When the cement parts are subjected to external tension, pressure, and bending force, these aragonite fibers can coordinate the solidified cement to absorb and migrate stress, further improve the mechanical strength of the cement parts, especially improve tensile, compressive, and bending properties. In addition, these aragonite fibers form a three-dimensional mesh distribution in the cement parts, which can effectively reduce the generation of microcracks inside the cement parts. When the cement parts are subjected to large stresses to produce fine cracks, the aragonite fibers are connected across the cracks to prevent the cracks from further growing and propagating, further improving the toughness and crack resistance of the cement parts.

[0064] Under normal cement hydration exothermic conditions, calcium carbonate crystal form will not be greatly affected. However, in order to reduce the conversion of aragonite fiber into calcite and better avoid the possible impact of cement hydration exothermicity, mineral admixtures such as fly ash, silica fume or slag can be introduced to effectively reduce the hydration heat and improve the long-term strength and durability of concrete. Or wet curing can be used to effectively reduce temperature fluctuations and make the cement hydration reaction more stable.

[0065] In some embodiments, the cement-based material can be cast and cured in a standard curing room for 28 days. During the curing process, the curing environment temperature is controlled to be 10-25°C to prevent the hydration reaction from exothermicly converting the aragonite fiber into calcite, ensuring that the aragonite fiber continues to play a microfiber modification role and improve the crack resistance of the cement product. The 7d flexural strength is measured to be up to 9.6MPa.

[0066] The following describes the invention in conjunction with specific embodiments.

[0067] Example A1

[0068] This embodiment provides aragonite fiber and a preparation method thereof, comprising the following steps:

[0069] S1. Extraction of calcium ions and sulfate ions:

[0070] Phosphogypsum and water were mixed in a solid-liquid mass ratio of 1:4, allowed to stand at room temperature for 1 hour, filtered and the upper clear liquid was retained to obtain a calcium ion solution. The calcium ion concentration was measured to be 1.5 mol / L, which also contained a small amount of sulfate ions.

[0071] S2. Extraction of biological urease and amylose:

[0072] Weigh 30g of soybeans and dry them at room temperature. Use an electric grinder to crush the soybeans. After crushing, the soybean powder is passed through a 100-mesh sieve. Weigh the filtered soybean powder and mix it with 1L of deionized water. Use a magnetic stirrer to stir it for 15 minutes. The stirred soybean powder solution is centrifuged for 30 minutes using a centrifuge. The temperature of the centrifuge is controlled at 20°C and the speed is 4000r / min. Discard the bottom sediment after centrifugation, filter the supernatant to obtain a soybean urease solution, i.e., a biological urease solution, in which the soybean urease concentration is 30g / L, and it also contains amylose.

[0073] S3. Preparation of aragonite fiber by precipitation reaction:

[0074] A urea solution with a concentration of 0.5 mol / L is provided, and the calcium ion solution obtained in step S1, the biological urease solution obtained in step S2, and the urea solution are mixed in a volume ratio of 1:1:2 to obtain a mixed solution, and a precipitation reaction is carried out at room temperature for 2 hours. After filtering again, the generated precipitate is rod-shaped aragonite.

[0075] Example A2

[0076] This embodiment provides aragonite fiber and a preparation method thereof, which is different from Embodiment A1 only in that the solid-liquid mass ratio of phosphogypsum to water in step S1 is changed from 1:4 to 1:10, and the rest are the same.

[0077] Example A3

[0078] This embodiment provides aragonite fiber and a preparation method thereof, which is different from Embodiment A1 only in that in step S2, 20 g of soybean raw material is weighed, and the concentration of the obtained soybean urease solution is 20 g / L, and the rest are the same.

[0079] Example A4

[0080] This embodiment provides aragonite fiber and a preparation method thereof, which is different from Embodiment A1 only in that the concentration of the urea solution selected in step S3 is changed to 1 mol / L, and the rest is the same.

[0081] Example A5

[0082] This embodiment provides aragonite fiber and a preparation method thereof, which differs from Embodiment A1 only in that in step S1, instead of using phosphogypsum for extraction, a calcium chloride solution with the same calcium ion concentration but without sulfate ions is provided, and the rest are the same.

[0083] Example A6

[0084] This embodiment provides aragonite fiber and a preparation method thereof, which differs from the embodiment A1 only in that: in step S1, phosphogypsum is not used for extraction, but a 1.5 mol / L pure calcium chloride solution is provided instead, which does not contain sulfate ions;

[0085] In step S2, a commercial pure biological urease solution is used, with the same concentration of 15 g / L and no amylose;

[0086] During the mixing process in step S3, a magnesium chloride solution is also added to the mixed solution so that the magnesium ion concentration in the final mixed solution is 0.5 mol / L, and the other aspects are the same.

[0087] Comparative Example A1

[0088] The difference between this comparative example and Example A1 is that the room temperature in step S3 is changed to 70° C., and the other conditions are the same. Finally, calcite is obtained in step S3.

[0089] Comparative Example A2

[0090] The difference between this comparative example and Example A1 is that the calcium ion solution in step S1 is not extracted through phosphogypsum, but is directly changed to 1.5 mol / L pure calcium chloride solution, and the soybean urease in step S2 is changed to commercial purified urease without amylose, and the other parts are the same. Finally, vaterite is obtained in step S3.

[0091] Comparative Example A3

[0092] The difference between this comparative example and Example A6 is that the magnesium chloride solution added in step S3 is replaced with a sodium chloride solution of the same amount and concentration, and the other parts are the same. Finally, vaterite is obtained in step S3.

[0093] Related performance tests and result analysis

[0094] The aragonite fibers provided in the above-mentioned Examples A1 to A6 and the products obtained in Comparative Examples A1 to A3 were analyzed by scanning electron microscopy to obtain SEM images, wherein the 2000-fold magnified image of the aragonite fibers in Example A1 is as shown in FIG. Figure 1 As shown, the 10000 times magnified image is as follows Figure 2 As shown; the 2000 times magnified image of the vaterite of comparative example A1 is as shown Figure 3 As shown, the 10000 times magnified image is as follows Figure 4 As shown; the 2000 times magnified image of the comparative example A2 calcite is as shown Figure 5 As shown, the 10000 times magnified image is as follows Figure 6 shown.

[0095] Figure 1 , Figure 2 It can be seen that the aragonite fibers in Example A1 have a rod-shaped microstructure, have a high aspect ratio, and are evenly distributed without the phenomenon of local agglomeration and adsorption into large particles. Figure 3 , Figure 4 It can be seen that the calcite in comparative example A1 is in a flaky microscopic shape and is locally agglomerated and adsorbed as secondary particles. Figure 5 , Figure 6 It can be seen that the vaterite in comparative example A2 is spherical in microscopic form, and is locally agglomerated and adsorbed into secondary particles.

[0096] Examples A1 to A4 all have sulfate ions and amylose as crystal stabilizers, Example A5 has only amylose as a crystal stabilizer compared to Example A1, Example A6 has only magnesium ions as a crystal stabilizer compared to Example A1, and Comparative Example A3 has only the lack of magnesium ions compared to Example A6, and no aragonite fiber is generated, which shows that chloride ions do not have the effect of crystal stabilization, confirming the role of magnesium ions. It can be seen that sulfate ions, amylose, and magnesium ions are all helpful in generating aragonite fibers.

[0097] Examples of cement-based materials and cement-made products:

[0098] The aragonite fibers provided in the above-mentioned Examples A1 to A6 and the products obtained in Comparative Examples A1 to A3 were respectively prepared into cement mortars according to the following mass proportions:

[0099]

[0100]

[0101] Then the product is cast into shape and cured in a curing room for 28 days with the temperature controlled at 20°C to obtain a cement product.

[0102] Among them, the aragonite fiber of Example A1 produced the cement product of Example B1, the aragonite fiber of Example A2 produced the cement product of Example B2, and so on, until the calcite of Comparative Example A1 produced the cement product of Comparative Example B1, the vaterite of Comparative Example A2 produced the cement product of Comparative Example B2, and the vaterite of Comparative Example A3 produced the cement product of Comparative Example B3.

[0103] Mechanical strength test

[0104] The performance tests were conducted on the cement products of the above-mentioned Examples B1 to B6 and Comparative Examples B1 to B3. The cement products were all test blocks of 40 cm×40 cm×160 cm, and in order to reduce the error, 3 test block samples were provided for each example or comparative example, and the average value of the test results was taken as the test result of the example or comparative example.

[0105] The cement mortar samples cured for 7 days were tested on a YYW-300DS cement compression and flexural integrated machine. The equivalent compressive strength and flexural strength tests were carried out at loading rates of 0.6 KN / s and 20 N / s. The test results are recorded in Table 1 below.

[0106] Table 1

[0107]

[0108]

[0109] As can be seen from Table 1, by using a mixed solution containing calcium ions, urea and urease for precipitation reaction, the amylose, magnesium ions and sulfate ions in the mixed solution will be conducive to inducing the formation of aragonite crystals, and combined with temperature control, the formation of vaterite and calcite will be reduced. The generated aragonite crystals are in the shape of microfibers, which is beneficial to improving the crack resistance of cement-based materials.

[0110] The crack resistance of each test block was evaluated by the above-mentioned flexural strength test. Comparative Example B1 is a test block made of calcite, so the test block has a higher compressive strength, but the flexural strength is significantly less than the embodiment of the test block made of all aragonite fibers, and does not have a high crack resistance. Comparative Examples B2 and B3 are test blocks made of vaterite, and the compressive performance is lower than the test block made of aragonite fibers, and the flexural performance is significantly lower. Therefore, compared with the performance comparison of comparative examples B1 to B3 with vaterite or calcite added to cement-based materials, aragonite fibers significantly improve the mechanical properties such as the crack resistance of cement-based materials.

[0111] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing aragonite fiber, characterized in that: The steps include: The raw materials including calcium ions, urea and a catalyst are prepared into a mixed solution for precipitation reaction to obtain aragonite fibers; Wherein, the mixed solution further comprises at least one of amylose, magnesium ions and sulfate ions, and the temperature of the mixed solution is ≤50°C.

2. The preparation method according to claim 1, characterized in that: In the mixed solution, the mass ratio of the calcium ion, the catalyst and the urea is 1:(0.5-2):(1-5); And / or, in the mixed solution, the concentration of calcium ions is 0.5 mol / L to 2.0 mol / L; And / or, in the mixed solution, the concentration of urea is 0.5 mol / L to 2.0 mol / L; And / or, in the mixed solution, the concentration of the catalyst is 20 g / L to 50 g / L.

3. The preparation method according to claim 1 or 2, characterized in that: When the mixed solution contains the amylose, the concentration of the amylose is 2% to 5%; and / or, when the mixed solution contains the magnesium ions, the concentration of the magnesium ions is 0.01 mol / L to 0.1 mol / L; And / or, when the mixed solution contains the sulfate ions, the concentration of the sulfate ions is 0.01 mol / L to 0.1 mol / L.

4. The preparation method according to claim 1 or 2, characterized in that: The temperature of the mixed solution is 20 to 50° C. And / or, the precipitation reaction time is 1 to 3 hours.

5. The preparation method according to claim 1 or 2, characterized in that: The catalyst includes urease, and at least one of the urease and the amylose is prepared from soybeans through a first extraction process; And / or, at least one of the calcium ions and the sulfate ions is obtained by subjecting phosphogypsum to a second extraction treatment.

6. An aragonite fiber, characterized in that: The aragonite fiber is prepared by the preparation method as claimed in any one of claims 1 to 5.

7. The aragonite fiber according to claim 6, characterized in that: The aragonite fiber satisfies at least one of the following characteristics (1) to (3): (1) Aspect ratio (3-6):1; (2) Length: 7 to 15 μm; (3) Specific surface area is 0.3 to 0.5 m 2 / g.

8. A cement-based material, characterized in that: The invention comprises cement material and also comprises aragonite fiber obtained by the preparation method according to any one of claims 1 to 5 or aragonite fiber according to claim 6 or 7.

9. The cement-based material according to claim 8, characterized in that: The mass ratio of the cement material to the aragonite fiber is (2-4):

1.

10. A cement product, characterized in that: The cement component is obtained by hydrating the cement-based material according to claim 8 or 9.

Citation Information

Patent Citations

  • Device for preparing calcium carbonate whiskers by CO2 mineralization and preparation method of calcium carbonate whiskers

    CN108588842A

  • Method for preparing different crystal forms of calcium carbonate by microbial mineralization

    CN109295108A

  • Aragonite type crystal seeds and aragonite type light calcium carbonate and preparation method thereof

    CN109467112A

  • Carbonation-accelerating high-strength composite starch mortar material and preparation method thereof

    CN114276099A

  • Micro rod-like aragonite type calcium carbonate and preparation method thereof

    CN115072757A

Cited By

  • Method for controllably preparing nanoscale calcium carbonate by taking regenerated micro powder as calcium source

    CN122212213A